GOVERNMENT AGRICULTURAL LENDING FROM THE PERSPECTIVE OF DEVELOPMENTAL INSTITUTIONS OPERATING IN THE PALESTINIAN JORDAN VALLEY - Qais HANTASH; Abdallah Ben SAAD; Bana BARGHOUTHI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The agricultural sector is a crucial component of Palestine's economy, contributing 6.5% to the GDP. The Jordan Valley, known for its fertile land and underlying eastern groundwater basin, is the focal point of this study. This research assesses governmental support as perceived by civil society organizations (CSOs), with an emphasis on the need for tailored lending programs. The study employs a descriptive-analytical methodology, utilizing questionnaires distributed to 20 CSOs. The findings suggest that effective lending programs should be coupled with agricultural guidance and consider seasonal production and marketing to enhance loan repayment feasibility.